Impact of aging on immature platelet count and its relationship with coronary artery disease. (16th November 2020) - Verdoia, Monica; Nardin, Matteo; Negro, Federica; Tonon, Francesco; Gioscia, Rocco; Rolla, Roberta; De Luca, Giuseppe
Abstract: Despite the fact that elderly patients represent a prevalent and challenging population in the current practice, few data exist on the impact of platelet parameters on cardiovascular risk in these patients. Therefore, the aim of the present study was to evaluate the impact of age on the immature platelet count (IPC) and their relationship with CAD. We included a total of 2236 consecutive patients undergoing coronary angiography in a single center. Elderly patients (age ≥ 75 years) were 756 (33.7%). IPC was measured at admission. Elderly patients were more often females ( p < .001), with lower BMI and prevalence of smokers ( p < .001), and a more complex cardiovascular risk profile and coronary disease ( p = .02). Platelet count decreased with aging ( p = .05), whereas no difference in the mean IPC was found between patients < or ≥75 years. In fact, advanced age did not emerge as an independent predictor of IPC above III tertile (≥8.6*10^6/ml), (adjusted OR[95%CI] = 0.97[0.78–1.21], p = .79). When considering elderly patients according to tertiles values of IPC (<5.1, 5.1–8.59; ≥8.6*10^6/ml), we found no impact of IPC on the prevalence of CAD (81.1% vs 84.5% vs 81.5%, p = .92; adjusted OR[95%CI] = 1.08[0.67–1.72], p = .75) and its extent (37.7% vs 34.5% vs 40.2%, p = .57; adjusted OR[95%CI] = 1.22[0.85–1.73], p = .28). However, we observed a higher rate of calcified and type C lesions in elderly patients with higher IPC ( p = .03 and p < .001, respectively). Therefore, advanced age is not associated with higher immature platelet count and the prevalence and severity of CAD. Moreover, IPC does not contribute to explain the higher prevalence and extent of coronary artery disease observed in elderly patients.